Assessment of POFA-pervious concrete performance with oil palm shells as a partial aggregate replacement - Mohd Faizal, Md Jaafar; Khairunisa, Muthusamy (Bentham Open, 2024)
Introduction: In Malaysia today, periods of excessive rain can result in flooding poses a significant challenge. The existing drainage system struggles to manage the wastewater effectively. In addressing the persistent issue of flooding in Malaysia, this issue’s solution was recommended to introduce pervious concrete (PC). Recognizing the urgency of finding sustainable and environmentally friendly solutions, the present study focuses on the application of PC as a potential remedy that allows water to infiltrate through its porous structure. Aims: Despite the potential benefits of PC, there exists a notable gap in the understanding of its performance, especially when incorporating oil palm shells (OPS) as a partial aggregate replacement in POFA-pervious concrete (PPC). OPS is an agricultural waste material abundant in palm oil-producing regions, remarkably in Malaysia. This research aims to bridge this gap to evaluate the performance of PPC and PPC with OPS. By addressing the performance of PPC at different OPS replacement levels and curing ages, the lack of such detailed investigations in the existing body of knowledge underscores the novelty and importance of this present research. Methods: Experimental tests were conducted to evaluate the performance of PPC and PPC incorporating OPS comprising density, water absorption, void content, and compressive strength. All the tests were conducted at 7 and 28 days after the hardened concrete was cured in water. Results: The results revealed that as the OPS content increased, the compressive strength of PPC with OPS decreased but was significantly higher than recommended in the standard. Conversely, the reduction in strength was accompanied by an improvement in water absorption, making PPC encompassing OPS suitable for applications. The void content of the PPC increased with higher OPS replacement levels, indicating an increase in porosity. This increase in porosity led to a decrease in the density of the PPC incorporating OPS. Conclusion: The findings of this research suggest that the incorporation of OPS as an aggregate replacement in PPC can offer advantages in terms of water absorption. The inclusion of 10% OPS significantly and positively affects the performance of PPC.